Toward a Critical Rethinking of Feminist Pedagogical Praxis and Resistant Male Students - Orr, Deborah (Canadian Journal of Education/Revue canadienne de l’éducation, 1993)
Feminist teachers increasingly confront resistant male students, but neither extant theoreti- cal nor practical literature provide much assistance in meeting this challenge. I argue that a critical theoretic analysis of masculinity that exposes its contradictions, in conjunction with an expanded concept of resistance, will help the feminist teacher develop a liberatory pedagogy for resistant male students (who are defending the status quo) by making the contradictions of masculinity visible to them; that is, by showing their position as simul- taneously oppressor and oppressed. Les enseignantes féministes se heurtent de plus en plus à la résistance de leurs étudiants masculins. Or, la documentation existante, qu’elle soit d’ordre théorique ou pratique, offre peu d’aide pour relever ce défi. L’auteure soutient qu’une analyse théorique critique de la masculinité mettant en évidence ses contradictions, de concert avec un concept élargi de la résistance, aidera l’enseignante féministe à développer une pédagogie libératrice pour les étudiants qui défendent le statu quo en leur montrant les contradictions de la masculinité, c’est-à-dire en leur faisant voir que leur position est à la fois celle d’un op- presseur et d’un opprimé.